Determination of mechanical parameters for soil-sand-tailings-cement mixtures for numerical modeling purposes - Vivian Cândido; Mario Riccio; Cátia Martins (REM: International Engineering Journal, 2025)
Abstract Brazil is a country with the second-highest production of iron ore in the world. As a consequence, tons of iron ore tailings (IOT) are generated, which constitutes an environmental liability. In this context, the present research aims to evaluate the potential for using IOT as raw material for making bricks or tiles, employing for example, the mixture soil-cement-sand-IOT. The objective is to determine mechanical parameters for this type of mixture to support future numerical analyses in a 3D environment in order to evaluate the potential of applying the mixture to the aforementioned elements. Therefore, a mixture of residual soil, IOT, sand and cement was prepared, and the Simple Compressive Strength Test was run to obtain the parameters of interest; additionally, analytical methodology obtained in literature was applied to determine other parameters of interest. After the experimental stage, computational simulations were conducted to verify whether the mechanical parameters obtained in laboratory tests and analytically are representative of the mechanical properties of the mixtures. The verification was carried out by comparing the results from simple compression tests with the results obtained via simulation of this test using the finite element method. Analyses were conducted using Plaxis 2D software. It was verified that the mechanical parameters obtained via simple compression tests and analytical equations are representative of the mechanical behavior of the mixtures, and therefore, such parameters can be used for numerical simulations of various components of civil construction. Thus, the mixture has potential for use, including other geometries, which also give this waste some value as a raw material in civil construction.